Online marketing strategy for Sidikalang Arabica Coffee Farmers by using the online marketplace in Desa Parbuluan VI Dairi - Hilman, Adrian (Talenta Publisher Universitas Sumatera Utara, 2021)
Desa Parbuluan VI is one of the villages in Dairi Regency, North Sumatra province, Indonesia. It was located at 1400 meters above sea level. Thus 60% of the people in Desa Parbuluan VI work as farmers, especially arabica coffee. The social engagement activities that have been carried out have focused on increasing the online market's understanding as a promotional tool for small business entrepreneurs and farmers in Desa Parbuluan VI. This activity aims to increase public awareness in using the online market and expand consumer reach to increase farmer products sales. Some of the methods used are by providing independent socialization and training in online market registration and management. The team immediately created a new account for farmers in online markets such as Tokopedia. Other activities include providing modules and sales support facilities such as product branding on the product packaging. This social engagement activity is expected to increase sales transactions and result in high economic turnover in raising the standard of farmers living in Desa Parbuluan VI.